STUNTING PREVENTION PROGRAM IN INDONESIA: A SYSTEMATIC REVIEW - Al Ansoriani, Marogi; Rahayu Kosasih, Dina Mentayani; Alam Al Ansoriani, Nuansa Nur (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Stunting is the result of inadequate birth and parenting, this is related to learning and barriers to community involvement. Therefore, the incidence and severity of stunting are indicators used for population assessment and can be useful for tracking the development of children in a population over time.The aim: This study aims to show the program of stunting prenetion in Indonesia. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 810 articles, whereas the results of our search on SagePub brought up 186 articles. The results of the search conducted for the last year of 2013 yielded a total 274 articles for PubMed and 73 articles for SagePub. In the end, we compiled a total of 20 papers, 3 of which came from PubMed and 17 of which came from SagePub. We included five research that met the criteria. Conclusion: Stunting is a state of nutritional disorder that is influenced by various factors, both regarding the condition of nutritional intake, knowledge of parents or the surrounding environment, as well as the role of government. So that in implementing the stunting prevention program, all concerned parties must be involved, starting from parents, community leaders, to government and non-government circles.